Neutron Energy Spectra and Yields from the 7Li(p, n) Reaction for Nuclear Astrophysics. Issue 1 (January 2016) - Tessler, M; Friedman, M; Schmidt, S; Shor, A; Berkovits, D; Cohen, D; Feinberg, G; Fiebiger, S; Krása, A; Paul, M; Plag, R; Plompen, A; et al.
Abstract: Neutrons produced by the 7 Li( p, n ) 7 Be reaction close to threshold are widely used to measure the cross section of s -process nucleosynthesis reactions. While experiments have been performed so far with Van de Graaff accelerators, the use of RF accelerators with higher intensities is planned to enable investigations on radioactive isotopes. In parallel, high-power Li targets for the production of high-intensity neutrons at stellar energies are developed at Goethe University (Frankfurt, Germany) and SARAF (Soreq NRC, Israel). However, such setups pose severe challenges for the measurement of the proton beam intensity or the neutron fluence. In order to develop appropriate methods, we studied in detail the neutron energy distribution and intensity produced by the thick-target 7 Li( p, n ) 7 Be reaction and compared them to state-of- the-art simulation codes. Measurements were performed with the bunched and chopped proton beam at the Van de Graaff facility of the Institute for Reference Materials and Measurements (IRMM) using the time-of-flight (TOF) technique with thin (1/8") and thick (1") detectors. The importance of detailed simulations of the detector structure and geometry for the conversion of TOF to a neutron energy is stressed. The measured neutron spectra are consistent with those previously reported and agree well with Monte Carlo simulations that include experimentally determined 7 Li( p, n ) cross sections, two-body kinematics and proton energy loss in the Li-target.